Nutritional Challenges in Duchenne Muscular Dystrophy - Salera, Simona (Nutrients, 2017)
Neuromuscular diseases (NMDs) represent a heterogeneous group of acquired or inherited conditions. Nutritional complications are frequent in NMDs, but they are sometimes underestimated. With the prolongation of survival in patients with NMDs, there are several nutritional aspects that are important to consider, including the deleterious effects of overnutrition on glucose metabolism, mobility, and respiratory and cardiologic functions; the impact of hyponutrition on muscle and ventilatory function; constipation and other gastrointestinal complications; chewing/swallowing difficulties with an increased risk of aspiration that predisposes to infectious diseases and respiratory complications; as well as osteoporosis with an associated increased risk of fractures. The aim of this review is to provide a comprehensive analysis of the nutritional aspects and complications that can start in children with Duchenne muscular dystrophy (DMD) and increase with ageing. These aspects should be considered in the transition from paediatric clinics to adult services. It is shown that appropriate nutritional care can help to improve the quality of life of DMD patients, and a multidisciplinary team is needed to support nutrition challenges in DMD patients. However, studies on the prevalence of overnutrition and undernutrition, gastrointestinal complications, infectious diseases, dysphagia, and reduced bone mass in the different types of NMDs are needed, and appropriate percentiles of weight, height, body mass index, and body composition appear to be extremely important to improve the management of patients with NMD.